DIVERSITY ANALYSIS OF DURIAN (Durio zibethinus Murr.) VARIETIES BY USING MICROSATELLITE MARKERS - Izzatun Nafsi (NIM. 106 02 027), Nur
Abstract: Durian (Durio zibethinus Murr.) is an important export commodity and has high economical value. As one of tropical countries with high biodiversity, Indonesia has more than 103 varieties of durian. In this study, polymorphism and genetic diversity between 10 durian varieties has been investigated by using microsatellite markers. Microsatellite markers are DNA sequences characterized by short (2-6 nucleotides) tandem repeats. They are highly polymorphic, locus specific, have high reproducibility. In this study, genomic DNA was extracted from leaves for PCR amplification of the microsatellite loci using seven pairs of microsatellite primers. Three of the seven pairs of microsatellite primers produced polymorphic alleles. The PCR products were resolved on non-denaturing polyacrylamide gels and stained with silver staining method. The number of polymorphic allele and polymorphism information content (PIC) were 6 allele/locus, and 0.719. Dendogram analysis showed two major groups. Group A consisted of durian Aden, Hepe, Petruk, Sunan, Sitokong, Matahari and Monthong. Group B consisted of Ajimah, D24 and Chanee. This study showed that the microsatellite markers (DZgccg01 dan DZcag01) can be used for detecting genetic diversity and polymorphism in durian.